2014
DOI: 10.1097/yct.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Is Electroconvulsive Therapy Use Among Young-Old and Old-Old Adults Comparable? A 10-Year Population-Level Analysis of Service Provision

Abstract: The higher ECT utilization rates we previously reported in older adults as a whole were further accentuated in old-old individuals. Old-old adults may have medical comorbidities and personal care needs that have implications for ECT technique and service delivery. Our findings underscore the need for greater inclusion of old-old patients in future ECT research to increase its clinical applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although there have been different attitudes towards the merits and disadvantages of electroconvulsive therapy (ECT) (Chung, ; Cong et al ., ; Huang et al ., ), it is still widely used in older patients in many parts of the world (Prudic et al ., ; Chanpattana, ; Plakiotis et al ., ). For example, in a postal survey, patients aged 65 years and above accounted for 38.4% of all ECT recipients in Australia (Chanpattana, ).…”
Section: Introductionmentioning
confidence: 97%
“…Although there have been different attitudes towards the merits and disadvantages of electroconvulsive therapy (ECT) (Chung, ; Cong et al ., ; Huang et al ., ), it is still widely used in older patients in many parts of the world (Prudic et al ., ; Chanpattana, ; Plakiotis et al ., ). For example, in a postal survey, patients aged 65 years and above accounted for 38.4% of all ECT recipients in Australia (Chanpattana, ).…”
Section: Introductionmentioning
confidence: 97%
“…German treatment guidelines follow a rather ECT-supportive path but limit the first-line indication for ECT to delusional depression, depressive stupor, schizoaffective psychosis with severe depressive mood, major depression with high suicidality or refusal to eat, and acute life-threatening pernicious catatonia ( Folkerts et al, 2003 ). The medical profession behind the statement has established that “refraining from ECT would mean an ethically unjustifiable restriction of the right of critically ill patients, who are often at risk for suicidal behavior, to get the best possible treatment.” In line with this position, review publications ( Kellner et al, 2020 ) and meta-analyses suggest to advertise ECT progressively to be used in a wider indication even in patients with potential risk profiles as ECT has been proven to be effective and safe during the first trimester of pregnancy ( Calaway et al, 2016 ) in children ( Døssing and Pagsberg, 2021 ) as well as in old-old adults aged 80 years and older ( Plakiotis et al, 2014 ; Kellner et al, 2016 ; McCall et al, 2018 ), and in patients with behavioral and psychological symptoms of dementia ( Swierkosz-Lenart et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…Data from a recent review of ECT studies conducted worldwide reported that one third of patients treated with ECT in Australia and New Zealand were over 65 years old, and 48-59 % of the patients treated in the USA were over 60 [12]. Moreover, reports on rates of ECT use suggest that older adults receive ECT at a higher rate than the overall population (e.g., 99.88 per 100,000 patients vs 37.85 per 100,000) [13][14][15] and that in fact, the highest rates of ECT use might be among the old-old population (>75-80 years old) [14].…”
Section: Electroconvulsive Therapy (Ect) Ect Use In the Elderlymentioning
confidence: 95%